Implementation of Child-Friendly School Innovation Policy in Sidoarjo Regency - Syapi’i Syapi’i; Aris Sunarya; Sri Kamariyah (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This research intends to examine the application of the Child-Friendly School (CFS) policy in Sidoarjo Regency, concentrating on its effects on educational quality, changes in school culture, and the efficiency of collaborative governance among involved parties. The research is based on the necessity to enhance secure, inclusive, and child-focused learning settings that align with the regional government’s dedication to transforming public education services. A qualitative case study method was employed, which included informants from the Education and Culture Office, school leaders, educators, and participants from child advocacy groups. The results indicate that the CFS policy in Sidoarjo has effectively improved student engagement, teacher awareness of humanistic methods, and collaboration among institutions to foster a positive learning environment. The implementation of the policy illustrates a transition in school culture from an emphasis on instruction to a compassionate learning environment. Additionally, digital advancements and data-based reporting systems have enhanced transparency and accountability. In summary, Sidoarjo’s CFS policy demonstrates an effective implementation of public value management and collaborative governance principles within education policy. The research suggests improving teacher abilities, reinforcing assessment systems, and increasing inter-sector cooperation to guarantee the program's sustainability